THE INVESTIGATING OF 360° VIDEOS ON SPEAKING SKILL APPLIED BY JUNIOR HIGH SCHOOL STUDENTS - M Toha (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
Abstract: This study aimed to find out the effectiveness of using 360° videos learning medium on speaking ability at junior high school students. In this study, the researcher used 360° videos in teaching speaking English at junior high school students. The research design of this study was quantitative pre-experimental one group pre-test and post-test design. The subjects of this study were 30 students from seventh grade of junior high school. There were two tests in this study, those tests were pre-test and post-test. In these tests, the subject of the study asked to describe people in the pre-test and describe place in the post-test. Before administered post-test, the subjects of this study were treated by 360° videos for three meeting. After treatment, the post-test was administered and analyzed the data (pre-test and post-test) using SPSS 22. In the analyzed the data, the researcher found the significant score was 0.000. It means that by using 360° videos learning medium in teaching speaking, the students achieve better score in speaking English than before students treated using 360° videos leaning medium.